2018
DOI: 10.1002/pen.24897
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and thermal degradation kinetics of short and long glass fiber reinforced PA10T composites

Abstract: In this work, the long glass fiber reinforced poly(decamethylene terephthalanide) (PA10T/LGF) composites and short glass fiber reinforced PA10T (PA10T/SGF) composites were prepared by two different extrusion processing methods, respectively. The results of mechanical properties reveal the introduction of glass fiber can improve the performance of the material, and the LGF reinforced PA10T composites can achieve much higher performance than the SGF reinforced ones at the same level of fiber contents. The therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Therefore, PA10T is always modified for use in practical applications. Traditionally, PA10T is mainly modified by the inclusion of a high content of glass fiber or other commonly used modified fillers [ 16 , 17 ]. However, the addition of high-content of glass fiber or other filler content significantly affects the comprehensive performance of PA10T.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PA10T is always modified for use in practical applications. Traditionally, PA10T is mainly modified by the inclusion of a high content of glass fiber or other commonly used modified fillers [ 16 , 17 ]. However, the addition of high-content of glass fiber or other filler content significantly affects the comprehensive performance of PA10T.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, L-FRPs have been intensely studied and are now widely used in the industry [ 5 , 6 , 7 ]. There are two commonly used types of processing technology used for glass fiber reinforced polymer composites: short glass fiber and continuous L-FRP composites [ 8 , 9 ]. L-FRP composites provide a better mechanical performance than short-fiber reinforced polymers (S-FRP).…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization peaks progressively become broader and lower as the IPA concentration rises, as shown in the graph's cooling DSC curves (Figure 2). As illustrated in the DSC data (Table 1), the crystallization temperature ( T c ) of samples gradually decreased with the increase in IPA content 26 . Moreover, the second heating DSC curves in Figure 3 showed that the samples' melting temperature ( T m1 and T m2 ) gradually decreased with the copolymerization proportions of IPA increased.…”
Section: Resultsmentioning
confidence: 83%